Personal Branding Melalui Media Sosial TikTok @Jihanmndaa - Zakiyah, Salsabila; Suryana, Cecep; Risdayah, Enok (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to find out how Jihan's character is in the three concepts of personal branding formed by Peter Montoya, namely First The Law of Specialization (Specialization), Second The Law of Visibility (Appearance), and Third The Law of Personality (Personality). This study uses interpretive qualitative research with the constructivism paradigm and descriptive qualitative methods using primary and secondary data. Observations, in-depth interviews were carried out in this study. The findings from the research conducted are that Jihan has fulfilled the concept of personal branding formed by Peter Montoya, namely: The Law of Specialization (Specialization) where in this concept, Jihan is productive and consistent, The Law of Visibility (Appearance) in this concept Jihan is able to attract public attention, up to date as well as interesting public speaking, and The Law of Personality (Personality) Jihan shows an interactive, friendly, and humble person.